PENGARUH LINGKUNGAN KERJA NON FISIK DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. BETON ELEMENINDO PERKASA DIVISI HRD & GENNERAL AFFAIR - Santi Dinar Amalia Alhidayah, - (2022)
This study aims to determine the description of the non-physical work environment, motivation and performance of employees at PT. Betonelemenindo Perkasa and to determine the effect of the Non-Physical Work Environment on employee performance. The Effect of Motivation on Employee Performance and to determine the effect of non-physical work environment and motivation on employee performance at PT. Beton Elementindo Perkasa. This study uses quantitative methods with a population and sample of 64 employees of PT. Betonelemenindo Perkasa Human Resource Department and General Affairs Division, using Nonprobability Sampling technique with Saturated Sampling. The analytical technique used is descriptive analysis, Pearson product moment correlation coefficient and multiple regression analysis. Hypothesis testing uses the F-Test to see the effect simultaneously and the -T-Test to see the partial effect. The results of this study indicate that the non-physical work environment and motivation have a significant effect on performance. Partially and positively the non-physical work environment has an effect on employee performance and motivation has a significant positive effect on employee performance. Keywords: Non-Physical Work Environment, Motivation and Employee Performance